2012
DOI: 10.1111/j.1753-4887.2011.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond overweight: nutrition as an important lifestyle factor influencing timing of puberty

Abstract: Early onset of puberty may confer adverse health consequences. Thus, modifiable factors influencing the timing of puberty are of public health interest. Childhood overweight as a factor in the earlier onset of menarche has been supported by prospective evidence; nonetheless, its overall contribution may have been overemphasized, since secular trends toward a younger age at menarche have not been a universal finding during the recent obesity epidemic. Current observational studies suggest notable associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 144 publications
(345 reference statements)
4
100
0
9
Order By: Relevance
“…However, the impact of the environment on menarcheal age may not be underestimated. Cheng et al [28] reported notable associations between dietary intakes and pubertal timing beyond contributions to an energy imbalance: children with the highest intakes of vegetable protein experienced pubertal onset up to 7 months later. Meanwhile, pubertal development might also be affected by spiritual and cultural factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of the environment on menarcheal age may not be underestimated. Cheng et al [28] reported notable associations between dietary intakes and pubertal timing beyond contributions to an energy imbalance: children with the highest intakes of vegetable protein experienced pubertal onset up to 7 months later. Meanwhile, pubertal development might also be affected by spiritual and cultural factors.…”
Section: Discussionmentioning
confidence: 99%
“…Quattro lavori hanno trovato una relazione tra maggiore assunzione di grassi totali o di acidi grassi polinsaturi (PUFA) e menarca più precoce [9]. -Assunzione di fibre.…”
Section: Fattori Ambientali Che Influenzano Lo Sviluppo Puberaleunclassified
“…Dziewczęta z wyż-szym wskaźnikiem BMI, będące przed menarche wzrastają szybciej niż ich rówieśniczki z niższym BMI [4]. Od stanu odżywienia zależy również metabolizm kostny.…”
Section: Dyskusjaunclassified